Oxidative damage and amyloid‐β metabolism in brain regions of the longest‐lived rodents. Issue 2 (22nd November 2013) - Edrey, Yael H.; Oddo, Salvatore; Cornelius, Carolin; Caccamo, Antonella; Calabrese, Vittorio; Buffenstein, Rochelle
<x xml:space="preserve">Abstract</x> Naked mole rats (NMRs) are the longest‐lived rodents, with young individuals having high levels of Aβ in their brains. The purpose of this study was twofold: to assess the distribution of Aβ in key regions of NMR brains (cortex, hippocampus, cerebellum) and to understand whether the accumulation of Aβ is due to enhanced production or decreased degradation. Recent evidence indicates that lipid peroxides directly participate in induction of cytoprotective proteins, such as heat shock proteins (Hsps), which play a central role in the cellular mechanisms of stress tolerance. Amyloid precursor protein processing, lipid peroxidation, Hsps, redox status, and protein degradation processes were therefore assessed in key NMR brain regions. NMR brains had high levels of lipid peroxidation compared with mice, and the NMR hippocampus had the highest levels of the most toxic moiety of Aβ (soluble Aβ1–42). This was due not to increased Aβ production but rather to low antioxidant potential, which was associated with low induction of Hsp70 and heme oxygenase‐1 as well as low ubiquitin‐proteasome activity. NMRs may therefore serve as natural models for understanding the relationship between oxidative stress and Aβ levels and its effects on the brain. © 2013 Wiley Periodicals, Inc.